Performance analysis of coherent free space optical communications with sequential pyramid wavefront sensor. (1st March 2018) - Liu, Wei; Yao, Kainan; Chen, Lu; Huang, Danian; Cao, Jingtai; Gu, Haijun
Highlights: The SPWFS is first applied to the coherent free space optical communications. The SPWFS is higher sensitivity than the Shack-Hartmann wavefront sensor. The SPWFS is more flexible spatial resolution than the Shack-Hartmann sensor. The AO system based-on SPWFS can increase ME and decrease BER effectively. The conclusions of this paper provide a new method of wavefront sensing. Abstract: Based-on the previous study on the theory of the sequential pyramid wavefront sensor (SPWFS), in this paper, the SPWFS is first applied to the coherent free space optical communications (FSOC) with more flexible spatial resolution and higher sensitivity than the Shack-Hartmann wavefront sensor, and with higher uniformity of intensity distribution and much simpler than the pyramid wavefront sensor. Then, the mixing efficiency (ME) and the bit error rate (BER) of the coherent FSOC are analyzed during the aberrations correction through numerical simulation with binary phase shift keying (BPSK) modulation. Finally, an experimental AO system based-on SPWFS is setup, and the experimental data is used to analyze the ME and BER of homodyne detection with BPSK modulation. The results show that the AO system based-on SPWFS can increase ME and decrease BER effectively. The conclusions of this paper provide a new method of wavefront sensing for designing the AO system for a coherent FSOC system.